Impact de l’artificialisation sur les ressources en sol et les milieux en France métropolitaine - Philippe Chéry (Unité Mixte de Recherche 8504 Géographie-cités, 2014)
The urban and suburban development is one of the most under-estimated causes of soil destruction. By using tools to characterize land use in the French metropolitan territory, the aim of this paper is to assess the phenomenon of artificialization and its impacts on soils and their environments. Three independent databases for evaluating soil artificialization were used : the TERUTI land use survey (SCEES), the urban area zoning database (ZAU-Insee) and Corine land cover (service de l’observation et des statistiques). The intersection between the different land use databases and the soil map of France at the scale of 1/1 000 000 (Inra, 1998) allowed us to characterize which soil types and which environments are most affected by artificialization. According to the three databases, the most threatened soils globally remain unchanged, with an artificialization rate above 50% of their surface : HISTOSOLS, FLUVIOSOLS dystriques, FLUVIOSOLS eutriques, NEOLUVISOLS, REDUCTISOLS and VERTISOLS. This list is completed by salty soils, according to the TERUTI land use survey. ANDOSOLS, PODZOSOLS, BRUNISOLS DYSTRIQUES, ALOCRISOLS, VERTISOLS and RANKOSOLS seem to be less affected by artificialization. The impact of artificialization was also assessed for each type of environment. The soils are grouped in three main types of environments : cultivated lands, forests and wetlands. The increase of artificialization highly affects wetlands, an environment for which there are major issues in terms of biodiversity, water quality and prevention of natural hazards.